Interference Coordination Based on POMDP in Multi-Cell OFDMA System - Qiang Wei; Tao Yang; Hui Feng; Bo Hu (Dianxin kexue)
The inter-cell interference coordination（ICIC）of OFDMA system was studied，and a dynamic ICIC algorithm based on the theory of partially observable Markov decision process（POMDP）was proposed.The statistic model of interference and SINR of channel was combined to allocate channels for cell-edge user in this algorithm.Simulation results show that the proposed scheme can efficiently avoid interference for the cell-edge user.Since this algorithm avoids the coordination between cells，the system overhead is saved.Furthermore，a likelihood relation between SINR and interference was established by using particle filter，so there was no necessary for system to measure the interference.